Ling hun de shi - Shi, Tiesheng 1951-2010 (Bai hua wen yi chu ban she, 2005)
Zusammenfassung
Essays
Keywords: Shi, Tiesheng / 1951-2010; Shi, Tiesheng / 1951-2010 / https://id.oclc.org/worldcat/entity/E39PBJw8V9CgP7vyPQKmWk6tKd; Sui bi / xian dai / zhong guo / zuo pin ji; Fiktionale Darstellung